ANALYSIS OF PARTICULATE MATTER (PM2.5) FLOUR DUST AND PERSONAL DUST SAMPLER (PDS) WORKERS IN THE CRACKERS ONION HOME INDUSTRY IN SIDOARJO, EAST JAVA, INDONESIA - Juharmanik, Prita; Azizah, R.; Faradina, Aulia; Kurniadi, Mohamad Edi; Eriani, Izmi Dwira (International Journal of Psychosocial Rehabilitation, 2020)
Background PM2, 5 has a composition consisting of sulphate, nitrate, organic compounds, ammonium compounds, metal and other contaminants that can cause health problems. Particulates derived from the home industry of onion crackers in Sidoarjo can cause health problems to workers. Purpose analyzes the levels of Pm2, 5 air flour dust and Personal Dust Sampler (PDS) workers in the home industry of garlic Crackers in Sidoarjo, East Java, Indonesia. Method is descriptive observational research with cross-sectional design. Measuring PM2, 5 using the EPAM 5000. Measurements of PM2 level of 5 workers using Personal Dust Sampler (PDS) were performed for 8 hours. A large sample is a total sampling of 15 workers. Result and Discussion showed the highest level of flour dust in the dough, compared to the frying pan and packing even though everything does not exceed the threshold value. It occurs because when the production process of dough making with flour raw material is being done. So the dust that is removed from the production process becomes more numerous. PM2, 5 in the highest working environment (6.411 mg/m3) at the dough part point meets the quality standards below 10 mg/m3. Rate PM2, 5 the highest worker is in the dough (2.0356 mg/m3) is still below the threshold value of 3 mg/m3. The higher the dust flour level PM2, 5 in the air the higher the personal dust level in the respondents with a value of contingency coefficient of 0.816, so it can be interpreted to have a very strong relationship. Conclusion the effort to decrease the dust level in the air using the dust collector engine as well as watering with water to avoid flying dust as well as planting trees for green open space in the home industry. Workers use routine masks, especially in the worker section of the cracker dough making. Home industry owners can more actively provide the personal protective equipment (PPE) that has been provided and disseminate and supervise the workers in the use of PPE.